(untitled) (Research, Society and Development, 2020)
Considering the changes in society, characterized by competitiveness, productivity, globalization, technological innovation and connectivity. Over the years, the expansion of Information and Communication Technologies (ICT) has been increasing significantly, what makes us reflect on its influence in education. That saíd, this study, through literature and field research, of an exploratory nature and qualitative, had as its central objective to investigate the use of ICTs in teaching and learning process of education in Natural Sciences in the areas of Chemistry, Physics and Biology, involving high school teachers in the public schools of Cascavel/PR, Brazil. For data collection it was used semi-structured script, which was applied in interviews with teachers, as well as a checklist to verify which ICT the schools have. The data obtained from the interviews were grouped into categories and their analysis took place using the Content Analysis Technique. The results made explicit, in the perception of teachers, that access and use of ICT in the classroom, can be one instrument of support, because it favors the presentation of the content, facilitates visualization and language, however, it is inferred that teachers must have continued training and that they are stimulated to think and use pedagogically the ICTs in the classroom.